PENGARUH KECERDASAN EMOSIONAL DAN MOTIVASI INTRINSIK TERHADAP PERILAKU INOVATIF GURU SEKOLAH DASAR - , Indira Fauzia Basrawy; , Dr. Ely Susanto, SIP., M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to examine the influence of emotional intelligence and intrinsic motivation on innovative behavior of elementary school teachers. There are two hypotheses in this study, namely (1): Emotional intelligence has a significant and positive influence on innovative behavior of teachers, (2) Intrinsic motivation has a positive and significant influence on the innovative behavior of teachers. Data collection method used a questionnaire on a number of elementary school teachers. Determination of the respondents used convenience sampling method, with consideration of the easy and efficiency. Analysis of data used multiple linear regression analysis, as well as T Test and F test using a significance level of 5%. Test results show that first hypothesis (H1), that emotional intelligence has a significant and positive influence on innovative behavior is acceptable. Second hypothesis 2 (H2), that intrinsic motivation has a positive and significant influence on innovative behavior can also be accepted. The conclusion of this study is emotional intelligence and intrinsic motivation has a positive and significant influence on innovative behavior of elementary school teachers.